Manajemen kemitraan sekolah dan masyarakat di sekolah dasar Telaga Pulang - Dona Pratiwi; Aslamiah Aslamiah; Ngadimun Ngadimun (Universitas Pendidikan Indonesia, 2026)
School-community partnership management is essential for improving the quality of primary education, especially in rural areas where schools rely heavily on community support. This study aims to describe and analyze the principals’ communication with the community, community empowerment, and models of school-community partnership management at SDN 1 Telaga Pulang and SDN 2 Telaga Pulang in Seruyan Regency, Central Kalimantan. This study employed a qualitative, multisite, descriptive design that involved principals, teachers, school committees, parents, and community members as informants. Data were collected through interviews, observations, and documentation, and then analyzed using interactive techniques of data condensation, display, and conclusion drawing at both single-site and cross-site levels. The findings show that principals apply informative, persuasive, dialogic, participatory, cultural, and digital communication patterns to build trust and strengthen school-community relationships. Community empowerment is implemented through enabling, empowering, and protecting strategies that foster participation in planning, implementing, and evaluating school programs. The partnership model reflects a mutualistic, two-way, symmetrical collaboration that supports academic, social, and infrastructural development in rural primary schools.